2015
DOI: 10.1590/s1519-99402015000200010
|View full text |Cite
|
Sign up to set email alerts
|

Zinco e vitamina E em dietas para frangos de corte criados em estresse calórico

Abstract: Objetivou-se avaliar o uso do zinco e da vitamina E em dietas para frangos de corte mantidos em cama reutilizada, no período de 1 a 21 dias de idade, sobre o desempenho, peso dos órgãos linfoides, digestivos e coração. Setecentos pintos distribuídos em um delineamento inteiramente casualizado, em esquema fatorial 2x3+1, sendo dois níveis de zinco (0,0 e 120mg/kg da dieta) associados a três níveis de vitamina E (0,0; 300 e 600mg/kg da dieta), uma dieta controle e cinco repetições, foram criados em galpões de al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(5 reference statements)
1
4
0
1
Order By: Relevance
“…The biometrics of the lymphoid organs (thymus, spleen, cloacal sac) was not influenced by the dietary organic zinc levels (Table 5). Similar results were found by Lopes et al (2015) who supplemented the diet of birds from 1 to 21 days to the level of 120 mg/kg of organic zinc. According to Feng et al (2010) The lymphoid organs such as thymus, spleen and cloacal sac have their weights increased linearly with the increase of dietary zinc.…”
Section: Levels Of Zinc (Mg/kg) CV (%)supporting
confidence: 84%
“…The biometrics of the lymphoid organs (thymus, spleen, cloacal sac) was not influenced by the dietary organic zinc levels (Table 5). Similar results were found by Lopes et al (2015) who supplemented the diet of birds from 1 to 21 days to the level of 120 mg/kg of organic zinc. According to Feng et al (2010) The lymphoid organs such as thymus, spleen and cloacal sac have their weights increased linearly with the increase of dietary zinc.…”
Section: Levels Of Zinc (Mg/kg) CV (%)supporting
confidence: 84%
“…Nevertheless, Lopes et al (2015) claimed that levels of zinc and vitamin E above the commonly used do not improve the feed intake, weight gain, feed conversion, production viability and the production efficiency index of broilers kept under high temperatures reared on reused litter.…”
Section: Referencesmentioning
confidence: 99%
“…The linear increase in the relative weight of the small intestine can be attributed to the fact that the size of the metabolically active viscera is reduced when birds are raised in environments above the thermoneutral zone, in order to promote the loss of heat to the environment (Lopes et al, 2015). Lopes et al (2015) found similar results, demonstrating a linear increase in absolute small intestine weight of broiler chickens fed increasing levels of alpha-tocopherol (300 and 600 mg/ kg). The small intestine is of fundamental The levels of alpha-tocopherol in the diets did not affect (p > 0.05) the relative weights of the heart, gizzard, liver, spleen, or bursa.…”
Section: Consistentmentioning
confidence: 78%
“…When combined with zinc (50 mg/kg feed), however, alpha-tocopherol (100 mg/kg feed) regulated the blood health indices and improved the performance of heat-stressed broilers (Hosseini-Mansoub, Chekani-Azar, Tehrani, Lotfi, & Manesh, 2010). Conversely, according to Lopes et al (2015), zinc (0 and 120 mg/kg diet) and alpha-tocopherol (0, 300, and 600 mg/kg diet) did not improve the feed intake, weight gain, production viability, or production efficiency index of broilers maintained for the first 21 days of life at high temperatures and reared on re-used litter.…”
Section: Introductionmentioning
confidence: 99%